2003
DOI: 10.1042/cs20020308
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of rat skeletal muscle function during storage for 16 h at 4 °C is not improved by pre-storage perfusion

Abstract: The aim of this study was to investigate if the preservation of isolated skeletal muscles for 16 h at 4 degrees C could be improved by pre-storage perfusion (PSP). Two rat muscle models were used: the soleus (SOL) and a posterior strip of the cutaneous trunci (CT). The effects of a 10 min PSP (at 25 degrees C) with University of Wisconsin solution (UW) or HTK-Bretschneider solution (HTK) on muscle function were analysed. The perfusion model was validated by the demonstration that the SOL and CT could be perfus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In a 2003 study, Van Der Heiden et al compared six perfused and six non-perfused muscle tissues to determine whether perfusion before storage at +4°C for 16 hours improves the properties of muscle tissues. [ 14 ] UW and HTK solutions were used for perfusion with both groups of muscle tissues incubated at +4°C for 16 hours. Comparison was conducted by measuring the function of the muscle tissue, and it was shown that perfusion did not yield any improvement of muscle tissue function.…”
Section: Discussionmentioning
confidence: 99%
“…In a 2003 study, Van Der Heiden et al compared six perfused and six non-perfused muscle tissues to determine whether perfusion before storage at +4°C for 16 hours improves the properties of muscle tissues. [ 14 ] UW and HTK solutions were used for perfusion with both groups of muscle tissues incubated at +4°C for 16 hours. Comparison was conducted by measuring the function of the muscle tissue, and it was shown that perfusion did not yield any improvement of muscle tissue function.…”
Section: Discussionmentioning
confidence: 99%
“…Flush-out with HTK (for composition, see [12]) at 4 • C was performed at a rate of 40 µl/min during 10 min [19] under continuous monitoring of perfusion pressure through the femoral artery catheter to ensure that high pressures in the cremaster muscle were avoided. Flush-out was not only performed to remove all blood cells from the cremaster muscle, but also to ensure that the entire vascular bed was filled with HTK during the ischaemic period.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, in 8 of 26 preparations the vascular territory supplied by the feed arteries of the RET was investigated by intravascular injection with plastic as described [19,20] . Briefly, 12 parts of Araldite F with 7.5% Microlith-T pigment was mixed with 4 parts of diluent DY 026 SP and 9 parts of hardener HY 2967 (all from Ciba-Geigy BV, Arnhem, The Netherlands).…”
Section: Vascular Territorymentioning
confidence: 99%